ORGANIC WASTE MANAGEMENT IN THE CONTEXT OF ENSURING THE ECOLOGICAL SAFETY OF THE REGION (INNOVATIVE ECONOMY, 2025)
Faifura V.V., Sydoruk B.O., Liubezna I.V. ORGANIC WASTE MANAGEMENT IN THE CONTEXT OF ENSURING THE ECOLOGICAL SAFETY OF THE REGIONPurpose. The aim of the article is to assess the structure and volume of biodegradable waste generation in agricultural production and the food industry of the Ternopil region, determine their potential as a secondary resource material, and substantiate the directions of forming a regional policy for the effective use of agro-industrial waste.Methodology of research. To prepare the scientific publication, methods of analysis and synthesis were applied, as well as a statistical method to assess the dynamics of volumes of crop production and the structure of bio-waste generation in the food industry within the Ternopil region; normalization – for researching the volume of bio-waste generation at the regional level, as well as systemic generalization – when forming conclusions and proposals.Findings. The volume of organic waste generation in key sectors of the agro-industrial complex of Ternopil region was estimated based on typical waste output standards from agricultural products. A structural analysis of the waste composition was conducted, which made it possible to identify the most significant sources of bioresources suitable for processing into organic fertilizers, biogas or other energy products. The potential resource and energy effect of involving agro-industrial waste in economic turnover was calculated, which demonstrates the economic feasibility of their utilization and processing. Originality. Directions for effective bio-waste management were proposed, emphasizing the connection between the problem of bio-waste management and environmental safety, which requires the integration of environmental, economic and management mechanisms within the framework of regional environmental policy.Practical value. The results of the analysis of the composition of the structure of bio-waste generation at the regional level are important from the perspective of forming a new environmental culture of bio-waste management at the level of territorial communities.Key words: organic waste, bio-waste, agriculture, environmental safety, region.
Keywords: organic waste; bio-waste; agriculture; environmental safety; region